Efektivitas E-Procurement (Pengadaan Barang Dan Jasa Secara Elektronik) Di Kabupaten Bone - Jusniati, Jusniati; Parawangi, Anwar; Wahid, Nur (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to find out how e-procurement (electronic procurement of goods and services) in realizing the effectiveness of e-procurement at the Electronic Procurement Service office in Bone Regency. This study used qualitative research methods to describe the conditions or phenomena that occured in the procurement of goods and services in Bone Regency. Objectively by using logic and appropriate theories in the field. The results of the study showed that: (1) target achievement, indicating that there was a target that has been determined through planning and then the target was achieved (2) adaptability, namely the ability to adapt to situations or circumstances that occured (3) job satisfaction, the work is said to be of high quality if it could provide satisfaction(4) Responsibility, after the division of tasks were required to carry out according to their respective jobs. Keywords: Effectiveness, E-procurement, Goods and Services